2013
DOI: 10.1186/1758-907x-4-1
|View full text |Cite
|
Sign up to set email alerts
|

Generation of a luciferase-based reporter for CHH and CG DNA methylation inArabidopsis thaliana

Abstract: BackgroundDNA methylation ensures genome integrity and regulates gene expression in diverse eukaryotes. In Arabidopsis, methylation occurs in three sequence contexts: CG, CHG and CHH. The initial establishment of DNA methylation at all three sequence contexts occurs through a process known as RNA-directed DNA methylation (RdDM), in which small RNAs bound by Argonaute4 (AGO4) guide DNA methylation at homologous loci through the de novo methyltransferase DRM2. Once established, DNA methylation at each of the thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 46 publications
0
20
0
Order By: Relevance
“…Previous reports showed that treatment with 5 μM/mL of the DNA methylation inhibitor 5-aza-2′-deoxycytidine (5-azadC) was effective in derepressing the transcriptional silencing of auxin-responsive ß-GUS reporter lines [ 35 ]. Treatment of Arabidopsis seedlings with 7 μM/mL 5-azadC also caused global changes in gene expression and derepression of silenced transgenes [ 36 , 37 ]. To investigate whether DNA methylation is involved in repressing GSTF8::LUC transgene expression, WT LUC , hsi2-2 LUC and hsi2-4 LUC seedlings were grown on media containing 5-azadC at various concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…Previous reports showed that treatment with 5 μM/mL of the DNA methylation inhibitor 5-aza-2′-deoxycytidine (5-azadC) was effective in derepressing the transcriptional silencing of auxin-responsive ß-GUS reporter lines [ 35 ]. Treatment of Arabidopsis seedlings with 7 μM/mL 5-azadC also caused global changes in gene expression and derepression of silenced transgenes [ 36 , 37 ]. To investigate whether DNA methylation is involved in repressing GSTF8::LUC transgene expression, WT LUC , hsi2-2 LUC and hsi2-4 LUC seedlings were grown on media containing 5-azadC at various concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…Tetrahydrofolate and its derivatives have long been recognized as one of the essential B vitamins in maintaining normal life because of their nutritional significance as well as crucial roles in one-carbon metabolism and epigenetic modification in living organisms (Hanson and Roje, 2001;Crider et al, 2012;Fitzpatrick et al, 2012;Lucock, 2000;Groth et al, 2016;Dinh et al, 2013). Thus, exploring folate homeostasis-associated biochemical reactions, cellular modifications, and underlying regulatory mechanisms are critical for people to improve the understanding of the important physiological functions of folates in plant development control and stressevoked plant adaptive responses.…”
Section: Discussionmentioning
confidence: 99%
“…RdDM is an important DNA methylation pathway in plants and has been extensively studied during the past two decades. Several forward and reverse genetics screens, including the ros1 suppressor screen in this study, were used to identify RdDM components 20,[31][32][33][34] . Through this ros1 suppressor screen, several novel RdDM mutants, such as rdm1, rdm4, and ktf1, were identi ed [21][22][23] .…”
Section: Discussionmentioning
confidence: 99%